Financial Literacy, Religious Attitudes Toward Online Gambling, and Their Impact on The Financial Well-Being of The Younger Generation - Asiroch Yulia Agustina; Masfiatun; Nurhadi Fadill; Muhammad Ashlyzan bin Razik (Jurnal Iqtisad, 2026)
This study is motivated by the increasing number of online gambling cases in Indonesia, which has developed into a serious social, economic, and financial well-being issue for society. West Java Province has recorded the highest number of online gambling cases in Indonesia, involving 535,644 individuals with a transaction value of approximately IDR 3.8 trillion. The high prevalence of online gambling has placed Indonesia in a state of financial health emergency. This study aims to examine and analyze the influence of financial literacy and religiosity on online gambling behavior, as well as its impact on the financial health of the younger generation in Parung District. This study employed a quantitative research design using path analysis with the assistance of SPSS software. The variables examined in this study were financial literacy (X1), religiosity (X2), online gambling behavior (Z), and financial health (Y). The results of Model I show that financial literacy and religiosity have a significant negative effect on online gambling behavior. Meanwhile, the results of Model II indicate that only financial literacy has a significant effect on financial health, whereas religiosity has no significant effect on financial health.